2017
DOI: 10.1002/slct.201701230
|View full text |Cite
|
Sign up to set email alerts
|

MB-UiO-66-NH2 Metal-Organic Framework as Chromogenic and Fluorogenic Sensor for Hydrazine Hydrate in Aqueous Solution

Abstract: Zirconium(IV)‐based MOFs UiO‐66‐NH2 and UiO‐66‐NH2 encapsulated with methylene blue (MB) MB‐UiO‐66‐NH2 were successfully prepared using a facile solvothermal method and were characterized by X‐ray diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), nitrogen physisorption analysis (BET), and X‐ray and photoelectron spectroscopy(XPS). Both the materials were 60–80 nm size and had large surface areas. MB‐UiO‐66‐NH2 appears to be a potential candidate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…Wagnerova et al [ 34 ] have reported that cobalt-tetrasulphophthalocyanines enhance the autoxidation process of hydrazines [ 34 ]. On the other hand, Ichiro Okura et al [ 35 ] reported that the autoxidation of hydrazine occurred with manganese (III)-hematoporphyrin at room temperature, and that has an advantage because of its reactivity for the formation of oxygen coordinated Mn(III)-Hm peroxide adduct [ 36 ]. Andrew P. Hong et al [ 37 ] reported that satisfactory autoxidation of hydrazines occurred using cobalt (II) 4,4′,4″,4‴-tetrasulfophthalocyanine (CoIITSP).…”
Section: Introductionmentioning
confidence: 99%
“…Wagnerova et al [ 34 ] have reported that cobalt-tetrasulphophthalocyanines enhance the autoxidation process of hydrazines [ 34 ]. On the other hand, Ichiro Okura et al [ 35 ] reported that the autoxidation of hydrazine occurred with manganese (III)-hematoporphyrin at room temperature, and that has an advantage because of its reactivity for the formation of oxygen coordinated Mn(III)-Hm peroxide adduct [ 36 ]. Andrew P. Hong et al [ 37 ] reported that satisfactory autoxidation of hydrazines occurred using cobalt (II) 4,4′,4″,4‴-tetrasulfophthalocyanine (CoIITSP).…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have been extensively used in dye adsorption due to their modifiable porous structure [33][34][35][36]. Furthermore, dye-incorporated MOFs have often been used for white light emission [37], the detection of nitro explosives [38], metal ions [39], organic molecules [40], photocatalysis [41], two-photon-pumped lasing [42], and solar cell manufacturing [43].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical techniques offer portable, quick, and economical methodologies, which has attracted the attention of researchers [10]. As hydrazine has strong reducibility, it is easy to oxidize on the surface of electrodes, and the electrochemical determination of hydrazine hydrate has been proven to be a feasible detection method [11]. To improve the sensitivity and reproducibility of hydrazine's reaction on electrodes, some functionalized nanomaterials have been used for the construction of hydrazine hydrate chemical sensors [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30]. Porous MOF-based sensors were also developed [11]. However, most MOFs are unstable in a water phase, so it is hard to apply them directly to electrochemical measurement in aqueous environment.…”
Section: Introductionmentioning
confidence: 99%